Vegetative Propagation of Forest Trees - Lahiri, A. K. (Indian Forester, 1979)
Trial was undertaken to find out the effect of auxins and (noo-auxinic) phenolic compounds on rooting of hitherto difficult to root material and easier materials. The results of the initial trial indicates the promising effect of auxin and non- auxinic chemicals. The effect of parahydroxy benxoic acid and indole-butyric acid is favourable to Populus gamblei, Dode, and Cryptomeria jrponica (L.f) Don. Further study is in progress to find at optimum concentration for each species.